2001
DOI: 10.1007/s004680100094
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative character variations of cambial derivatives in mangroves and their functional significance

Abstract: Quantitative character variations of xylem cambial derivatives during secondary growth of the trunk are described for five representative mangrove species: Rhizophora stylosa (Rhizophoraceae), Bruguiera gymnorrhiza (Rhizophoraceae), Kandelia candel (Rhizophoraceae), Sonneratia alba (Sonneratiaceae) and Avicennia marina (Avicenniaceae). Two variation patterns in tracheary element length were revealed among these species. For R. stylosa, A. marina and S. alba, both vessel elements and fibers showed an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Barghoorn (1941) suggested that in species with multiseriate rays there is a tendency towards increased ray width, pith to bark. Our study supports the Barghoorn suggestion (1941) and we also note that, contrary to this tendency, there was a decrease in the ray frequency towards the periphery of the stem and that for these characteristics, the mean values varied little between radial positions distant from the pith, behavior reported in previous studies (Sun and Suzuki 2001, Rahman et al 2005, Tsuchiya and Furukawa 2010).…”
Section: Effect Of Radial Positionsupporting
confidence: 93%
“…Barghoorn (1941) suggested that in species with multiseriate rays there is a tendency towards increased ray width, pith to bark. Our study supports the Barghoorn suggestion (1941) and we also note that, contrary to this tendency, there was a decrease in the ray frequency towards the periphery of the stem and that for these characteristics, the mean values varied little between radial positions distant from the pith, behavior reported in previous studies (Sun and Suzuki 2001, Rahman et al 2005, Tsuchiya and Furukawa 2010).…”
Section: Effect Of Radial Positionsupporting
confidence: 93%
“…Lovelock unpublished data). In addition, high levels of variability in xylem characteristics (Sun & Suzuki 2001; Yanez‐Espinosa, Terrazas & Lopez‐Mata 2001) and stem hydraulic conductivity (Sperry et al . 1988; Melcher et al .…”
Section: Discussionmentioning
confidence: 99%
“…The high variation in hydraulic conductance of stems were in the range of those measured for R. mangle by Sperry, Tyree & Donnelly (1988b) and Melcher et al . (2001), and reflect the highly variable xylem anatomy of this species (Sun & Suzuki 2001). These data suggest that both N and P availability limit the production and/or activity of meristems, while the large number of nodes per length in control plants compared to P‐fertilized plants (Table 3) suggests that availability of P strongly limits cell expansion rates (Grossman & Takahashi 2001), which probably affects the length and width of xylem vessels and the porosity of their pit membranes, properties that determine their hydraulic conductance (Tyree & Ewers 1996; Comstock & Sperry 2000).…”
Section: Discussionmentioning
confidence: 99%